21世纪中国电影英雄的塑造 = The making of a 21st century China film hero - 佘曜丞 Seah, Walter Yao Chen (Nanyang Technological University, 2020)
英雄，一个在人们心目中的伟大形象及理想榜样。从远古时期的崇拜开始，英雄形象为符合时代的需求，即要拥有历代英雄所拥有的性质外，也必须具有被现代社会认可的性质。对此，随着时代的变迁，英雄的形象逐渐变得越加复杂，并在一脉传承下，演变成了现当代世人所认同的形象。因此，本文开篇将探讨不同学界对于英雄的定义，从中挖掘英雄形象的重要性。之后，篇章范围将浓缩到中国学界当中，并在其英雄形象的理解下，展示出历代中国英雄形象上所拥有的共同性质。接着，本文再会以21世纪中国电影英雄为范围，探讨现当代中国电影何以塑造其银幕英雄，展示出银幕英雄形象上的塑造与演变。最后，本文将会以笔者对于未来中国电影英雄形象的展望作为文章的结语。A hero, a great and ideal role model in the hearts of the people. From the beginning of the ancient times of worship, the image of a hero was crafted based on the times that it appears, showing that not only does a hero requires the qualities that its predecessors have, but it also must consist of the qualities that are recognized by the modern age as well. Thus, as time flows, the passing down of the image of the hero has made it more complex, gradually taking shape to be one that is known in the today’s world. Hence, this paper will first begin with a discussion on how different academics from various research sectors view on the topic of what defines a hero, therefore, showing the importance of the image of a hero. After which, discussions will be made on how the Chinese view the heroic image and the qualities that past hero figures had inherited in the history of China. Following that, the paper will narrow its scope to 21st century China films, examining how the image of the hero has changed and evolved on the silver screen. Finally, the paper will end off with the author’s inputs on regards to the future of the heroic image in China.